1998
DOI: 10.1056/nejm199812033392301
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy Compared with Autologous or Allogeneic Bone Marrow Transplantation in the Management of Acute Myeloid Leukemia in First Remission

Abstract: A postinduction course of high-dose cytarabine can provide equivalent disease-free survival and somewhat better overall survival than autologous marrow transplantation in adults with acute myeloid leukemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
335
1
11

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 548 publications
(363 citation statements)
references
References 31 publications
16
335
1
11
Order By: Relevance
“…The role of ASCT in AML remains controversial. Phase II and III trials showed that ASCT provides lower relapse rates than conventional CHT and improves DFS in some but not in all studies [3,[7][8][9]. Our retrospective study analyzed the role of ASCT in patients with AML, with good, intermediate and poor prognostic features.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of ASCT in AML remains controversial. Phase II and III trials showed that ASCT provides lower relapse rates than conventional CHT and improves DFS in some but not in all studies [3,[7][8][9]. Our retrospective study analyzed the role of ASCT in patients with AML, with good, intermediate and poor prognostic features.…”
Section: Discussionmentioning
confidence: 99%
“…In table 3 we compared our results with three large phase III randomized studies [7][8][9], ALWP-EBMT registry [10] and two recent long-term single institution studies [1,4]. It is now well proven that hemopoiesis recovery (engraftment) is more rapid with PBSCT than with BMSCT [11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…As reported in other series [28,45], 25% of eligible patients failed to receive stem cell grafts due to several reasons, including refusal to undergo further therapy. While the groups may not be comparable, patients who completed consolidation treatment but failed to undertake stem cell transplantation had an overall poor outcome (Fig.…”
Section: Discussionmentioning
confidence: 61%
“…Whether such patients should receive high-dose ara-C based chemotherapy alone or undergo autologous or allogeneic stem cell transplantation remains unsettled. Several large prospective studies have failed to demonstrate a consistently superior survival for one therapy over another [38,39]. Most, [40,41]but not all, [42] trials have failed to document a benefit for the addition of low dose (maintenance) chemotherapy after intensive post-remission therapy.…”
Section: Discussionmentioning
confidence: 99%